Community Engagement Through Health Education on Tuberculosis (TB) During World Pharmacist Day 2025 - Nanda Asyura Rizkyani; Nhestricia, Nhadira; Setiani, Lusi Agus; Gunawan, Wawan; Yenni, Tengku (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
Tuberculosis (TB) remains a major public health challenge in Indonesia. Pharmacists play a crucial role in strengthening community awareness, promoting early detection, and supporting treatment adherence. Community education activities are essential to empower the public with accurate knowledge and preventive practices. To describe the implementation and outcomes of TB health education conducted as part of the World Pharmacist Day (WPD) 2025 celebration in Bogor City and to evaluate its contribution to improving community awareness regarding TB. A community engagement activity was conducted on 25 September 2025 at Taman Heulang, Bogor. The program included health promotion through group exercise, pharmacist-led TB education, distribution of educational media, and direct one-on-one counseling. Preparatory activities, collaboration with stakeholders, and dissemination of 700 educational materials were documented. The activity involved 268 participants from IAI Kota Bogor and more than 300 community members attending the routine exercise program. TB education delivered by the Kopi TB team improved participants’ understanding of TB symptoms, transmission, prevention, and treatment adherence. Educational flyers and stickers served as effective reinforcement tools, expanding information reach within the community. The collaborative approach between pharmacists, local health authorities, and community groups facilitated high engagement and smooth execution of the program. The WPD 2025 community engagement activity successfully enhanced public awareness of TB and demonstrated the vital role of pharmacists in health promotion. Continued multidisciplinary collaboration is recommended to strengthen community-based TB control efforts.